1985
DOI: 10.1002/ar.1092120216
|View full text |Cite
|
Sign up to set email alerts
|

Variational anatomy of the deep femoral artery

Abstract: The deep femoral artery is frequently incorporated in vascular reconstructive procedures in the proximal leg. To study the branching variations of this artery, we dissected 100 legs and then classified the anatomical patterns. The deep femoral artery originates a median distance of 4.4 cm from the inguinal ligament. The origin of the lateral circumflex artery varied greatly. When it branched from the deep femoral, the origin of the lateral circumflex was 1.5 cm (median) from the origin of the deep femoral. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
3
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 8 publications
9
53
3
1
Order By: Relevance
“…This indicates that the origin of the right profunda is usually distal to the origin of the left profunda femoris by 0.365 cm, which is similar to the study by Bannister et al, but more than the average distance of origin has been reported by Snell 4 cm, Siddharth et al 4.4 cm, and Dixit et al 4.75 cm [1,4,6,7]. High origin of PFA can cause problems in procedures such as femoral arterial and venous puncture and femoral nerve blocks because of the close relationship between vessels and nerves in the femoral triangle.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This indicates that the origin of the right profunda is usually distal to the origin of the left profunda femoris by 0.365 cm, which is similar to the study by Bannister et al, but more than the average distance of origin has been reported by Snell 4 cm, Siddharth et al 4.4 cm, and Dixit et al 4.75 cm [1,4,6,7]. High origin of PFA can cause problems in procedures such as femoral arterial and venous puncture and femoral nerve blocks because of the close relationship between vessels and nerves in the femoral triangle.…”
Section: Discussionsupporting
confidence: 87%
“…Many authors reported that the usual origin of MCFA was from profunda femoris in 79 % by Tanyeli et al, 64 % by Siddharth et al, 62.5 % by Dixit et al, and 83.3 % by Gautier et al [4,7,9,10], but we found only 50 % of Fig. 1 (continued) MCFA from PFA and a common stem of origin for both MCFA and PFA in 7.5 %.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The average distance of the origin of lateral circumflex artery from the profunda femoris artery in our study is found to be 21.2mm which is similar to the observation made by Prakash et al 6 (25mm).It was found to be as high as 48mm± 12mm in Turkish population 8 and as low as 15mm in Indian population 5 .…”
Section: (42mm)supporting
confidence: 90%